ANALYSIS OF LOCAL REVENUE (PAD) OF MOROWALI DISTRICT - Jaya, Andi Herman (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Local governments in Indonesia are increasingly focusing on financial independence and efficiency to support regional development. Morowali Regency, located in Central Sulawesi Province, is no exception. As regional autonomy policies have been implemented, it has become crucial to assess the financial performance of local governments. This assessment helps determine their capacity for self-governance and efficient resource management. Key indicators in this evaluation include the Independence Ratio, Effectiveness Ratio, and Efficiency Ratio of Regional Original Income (PAD). This study aims to analyze the Independence Ratio, Effectiveness Ratio, and Efficiency Ratio of Morowali Regency's Regional Original Income. The research employs calculations of these ratios for Local Revenue. Results show that the Independence Ratio had an average value of 24.97 percent, falling within the medium independence criteria. This indicates that the region has not yet achieved full independence. The average Effectiveness Ratio is 2.68 percent, reflecting that the realization of Regional Original Income (PAD) is greater than the target set by the Morowali Regency Government, suggesting effective task execution. The average Efficiency Ratio is 1.72 percent, meaning that the realized PAD obtained by Morowali Regency exceeds the costs incurred in collecting it. This indicates efficient PAD collection, as the realized income is greater than the budget allocated for its collection.